2020
DOI: 10.1002/suco.201900482
|View full text |Cite
|
Sign up to set email alerts
|

Effect of macro polypropylene fiber and basalt fiber on impact resistance of basalt fiber‐reinforced polymer‐reinforced concrete

Abstract: In this paper, the effect of macro nonmetallic fibers (i.e., polypropylene fibers and basalt fibers) on the impact response of basalt fiber‐reinforced polymer‐reinforced concrete (FRP‐RC) discs is experimentally investigated using a self‐developed drop‐weight impact test device. The plain concrete and conventional steel‐reinforced concrete samples are explored as references. The impact resistance and failure behaviors are analyzed. Statistical analyses for first‐crack strength and failure strength are performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 40 publications
0
12
0
2
Order By: Relevance
“…The main advantages of using synthetic macrofibers as concrete reinforcement are: (1) minor impact on the workability of the fresh concrete; (2) these are inert to chlorides and aggressive chemicals that can affect to steel reinforcement and/or concrete [14][15][16] ; and (3) in case of fibers remain at surface of the pipes, these hardly can cause injuries to labors due to its flexibility. Some authors [17][18][19][20][21] have even concluded that polypropylene macrofibers (PPFs) can be more efficient (for a certain range of fiber volumes and mechanical requirements) than SFs for increasing toughness and post-cracking residual strength of concrete.…”
mentioning
confidence: 99%
“…The main advantages of using synthetic macrofibers as concrete reinforcement are: (1) minor impact on the workability of the fresh concrete; (2) these are inert to chlorides and aggressive chemicals that can affect to steel reinforcement and/or concrete [14][15][16] ; and (3) in case of fibers remain at surface of the pipes, these hardly can cause injuries to labors due to its flexibility. Some authors [17][18][19][20][21] have even concluded that polypropylene macrofibers (PPFs) can be more efficient (for a certain range of fiber volumes and mechanical requirements) than SFs for increasing toughness and post-cracking residual strength of concrete.…”
mentioning
confidence: 99%
“…The coarse PPF has all most the same enhancement on strength and toughness compared with steel fiber. Besides, coarse PPF is of excellent anti‐electromagnetic interference, therefore, the study on mechanical properties of concrete reinforced with coarse and fine PPF has higher social and economic benefits 15,24–26 …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, macro‐synthetic fibers have better features in density and corrosion resistance compared with steel fibers 16 . Moreover, macro‐synthetic fibers can bridge crack, control crack width, consume energy, and provide residual flexural tensile strength for concrete 17 . Characteristically, the performances of fiber‐reinforced concrete depends on a number of factors: matrix characteristics, fiber characteristics (elastic modulus, tensile strength, surface feature, and fiber size), and mix characteristics (fiber content, distribution, and orientation).…”
Section: Introductionmentioning
confidence: 99%
“…16 Moreover, macro-synthetic fibers can bridge crack, control crack width, consume energy, and provide residual flexural tensile strength for concrete. 17 Characteristically, the performances of fiber-reinforced concrete depends on a number of factors: matrix characteristics, fiber characteristics (elastic modulus, tensile strength, surface feature, and fiber size), and mix characteristics (fiber content, distribution, and orientation). To date, some investigations [18][19][20] have been performed on the fiber content, distribution, orientation, and matrix strength of macrosynthetic fiber-reinforced concrete.…”
Section: Introductionmentioning
confidence: 99%